Attitude of Agricultural Science Students and their Parents toward Agricultural and Forestry Career in Ibadan North Local Government Area of Oyo State, Nigeria - Appah, Ogechukwu R.; Tunde-Francis, Anne A.; Amadi, Joyce O. (NIU Journal of Humanities, 2022)
The purpose of this study was to assess secondary school students and their parents’ attitude towards agriculture and forestry career and the relationship that exist between their attitudes. Multistage sample technique was used to sample one hundred and eighty (180) students for the study and through the students 180 parents were included. A validated questionnaire known as Students/parents’ Attitude towards agricultural/Forestry career was used to collect data for this study (students’ attitude r = 0.83 and parents’ attitude r=0.84). Descriptive statistics (frequency and percentage) and Pearson r was used in data analysis. The results showed that students and their parents’ attitude towards agriculture and forestry career were negative. In addition, there was a significant relationship between students’ attitudes and parents’ attitude towards agricultural and forestry career (Pearson r=209). It is therefore recommended that there should be sensitization in schools both for the students and Parents Teachers association meetings to educate both the students and parents on importance and benefits of agricultural/forestry career. Keywords: Attitude, Agriculture, Forestry, Students, Parents